2020
DOI: 10.4028/www.scientific.net/kem.844.38
|View full text |Cite
|
Sign up to set email alerts
|

Conditions of Suitability of Coal Seams for Underground Coal Gasification

Abstract: Results of evaluating the suitability of certain sections of Western Donbas coal seams, based predominately on properties of coal material, for their further experimental development by means of underground gasification method are represented. Criteria to evaluate both expediency of underground gasification and specific conditions of that process are substantiated basing upon the methodology developed at the National Mining University (Dnipro, Ukraine) together with representatives from National University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Describes use of underground haulers with 50t capacity in gold mining. The authors stress the necessity of implementing high-level mechanization of all ore mining operations [29][30][31][32]. Thus, according to the authors, the tunneling speed of up to 150 m/month is achieved due to application of three "Boomer" drilling rigs.…”
Section: Resultsmentioning
confidence: 99%
“…Describes use of underground haulers with 50t capacity in gold mining. The authors stress the necessity of implementing high-level mechanization of all ore mining operations [29][30][31][32]. Thus, according to the authors, the tunneling speed of up to 150 m/month is achieved due to application of three "Boomer" drilling rigs.…”
Section: Resultsmentioning
confidence: 99%
“…In the model studies conducted by Otto et al [44] and Nakaten et al [45], the width of the gasification channel was often assumed to be 20 m. Pivnyak et al [46] determined that the range of the impact of high temperature in the roof and floor can reach values up to 5.7 and 3.2 thickness of the gasified coal seam, respectively. Experiments conducted in Russia showed that, depending on the type of rock, due to the heating of the roof, rocks in the cave zone may be in the range of 1.33-3.8 m, and the metamorphized zone of rocks is from 0.65 m to 0.84 m [47].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the valid results of the modelling in terms of the experimental stand unit that would help get the data for field conditions, a group of similarity invariants, characterizing the gasification process, were considered [98]:…”
Section: Similarity Criteriamentioning
confidence: 99%